دراسة صدأ قضبان التسليح ضمن البيتون مع وبدون حماية - تريكية, علي; خيربك, علي; زيزفون, مقداد (Latakia University Journal -Engineering Sciences Series, 2019)
تعتبر مادة البيتون المسلح من أكثر مواد البناء انتشاراً في العالم. ويعود السبب في ذلك إلى أنها لا تحتاج إلى خبرةٍ فنيةٍ عالية للتنفيذ، وتمتلك ديمومةً مقبولة يمكن رفعها إذا ما تم تحسين خصائص البيتون. وتعتبر ظاهرة الصدأ من أكثر العوامل التي تؤدي إلى فقدان ديمومة البيتون المسلح، ويأتي خطر الصدأ من إمكانية تطوره حتى يخرّب التسليح بشكلٍ كامل، فيخرج العنصر البيتوني من الخدمة. وتقدر الكلفة السنوية لإصلاح الجسور المتضررة، على سبيل المثال، نتيجة الصدأ في الولايات المتحدة الأمريكية نحو (10 بليون دولار)[4]، وهذا ما يظهر ضرورة العناية بالبيتون، وحمايته قبل أن يبدأ تخربه. يهدف هذا البحث إلى دراسة تأثير الصدأ في القضبان الفولاذية ضمن البيتون مع وبدون طلاء حماية، وذلك من خلال إجراء تجارب التأكل المسرع على العينات، ذات القضبان الفولاذية المطلية، وغير المطلية بمادة الإيبوكسي، وإجراء اختبار الشد المباشر على العينات السليمة، والمعرضة للتأكل المسرع كلها، ودراسة كل من المتغيرات (مقاومة البيتون - حماية القضبان الفولاذية بمادة الإيبوكسي)، وتأثيرها في زمن بدء التأكل وفي إجهاد التماسك بين البيتون والفولاذ. وأظهرت نتائج هذه التجارب الارتباط الوثيق بين جودة البيتون والزمن اللازم لبدء التأكل، والدور الإيجابي لطلاء فولاذ التسليح بالإيبوكسي من خلال تأخيره الكبير لزمن بدء التأكل، وإضعافه النسبي لإجهاد التماسك. The reinforced concrete is considered as the most famous material for construction in the world. The reason is that it does not need high experience to execute, in addition to it has a good durability which can increased if the concrete is improved. The corrosion is considered the main factory which cause to loss the durability of reinforced concrete. The dangerous of corrosion that it continue until destroy the reinforced completely and the element be out of use. The annual cost to repair the bridges in U.S.A (for example) is estimate about (10 Billion $),So it's important to protect concrete before damage. The research aim is to study the influence of corrosion on the steel bars in reinforced concrete with/without paint protection. by performing the accelerated corrosion tests on the specimens have (coated by epoxy, without epoxy) bars and performing the bond test through direct tensioned experiment on the specimens (exposed to accelerated corrosion, normal),and studding the changes (concrete resistance - protect the steel bars with epoxy) and it's influence on the time of corrosion & bond stress between concrete and steel. These tests show the relation between the quality of concrete and the required time for corrosion, and the positive turn of the epoxy coat in retardation the time of corrosion and it's relation reduction on bond stress.